Research on shipping carbon governance considering rent-seeking behavior: an evolutionary game analysis based on prospect theory - Chen, Qing; Chen, Fang; Gu, Bojun; Tian, Peng; Fu, Yufang (Frontiers in Marine Science, 2025)
Accurate carbon emission data serve as the foundation for the effective functioning of carbon markets. However, strategic collusion driven by perceived utility values among market participants can systematically erode governance efficacy. In response to the vulnerability of shipping carbon governance systems caused by rent-seeking behavior, this study develops a tripartite evolutionary game model involving shipping companies, carbon verification agencies, and governments based on prospect theory. Using system dynamics modeling and numerical simulation, we validate the equilibrium constraints and analyze the impact of basic parameters and perceived value coefficient. The results indicate that shipping carbon governance evolves dynamically in stages across its lifecycle, driven by the formation of self-sustaining in shipping companies. Moreover, stakeholder decisions predominantly determined by cost-benefit structures, wherein ESGs’ green premiums effectively drive low-carbon transition, while the anticipated rent-seeking gains incentivize such collusion. Additionally, perceived coefficients exert differentiated moderating effects. Shipping companies’ transition decisions show negative correlations with the risk attitude and loss aversion coefficients, whereas carbon verification agencies and governments demonstrate overall positive correlations with these coefficients. Consequently, we propose a systematic governance framework to provide decision support for solving the rent-seeking dilemma and promoting a carbon governance in shipping industry.